Lung involvement in Sjögren's syndrome: a comparison between patients with primary and with secondary syndrome. Issue 7 (July 1985) - Vitali, C; Tavoni, A; Viegi, G; Begliomini, E; Agnesi, A; Bombardieri, S
Abstract : Lung function was assessed in 20 patients with primary Sjögren's syndrome (SS) and in a group of patients with SS associated with a variety of connective tissue diseases. Signs of small airway disease and of altered diffusion capacity, together with chest x-ray features of mild interstitial involvement, were the most common findings in primary SS. On the whole, lung involvement was more frequent and severe in patients with the secondary form of the syndrome. In both primary and secondary SS lung function changes did not correlate with the other clinical and serological parameters, except for a more severe impairment of diffusion capacity in patients with Raynaud's phenomenon.